1995
DOI: 10.1159/000106929
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Estrogen Replacement Therapy in Female Patients with Dementia of the Alzheimer Type: 7 Case Reports

Abstract: Seven female patients with mild to moderate dementia of the Alzheimer type (DAT) were treated with long-term, low-dose estrogen replacement therapy (ERT) over a period of 5–45 months. Five of the 7 patients were cases who had responded well to short-term ERT with 1.25 mg/day of conjugated equine estrogens (CEE) for 6 weeks. The 7 patients from 56 to 77 years of age received 0.625 mg/day of CEE for 21 days, followed by a pause of 7 days. A28-day cycle of low-dose ERT was performed repeatedly. In 4 cases, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 26 publications
3
47
0
1
Order By: Relevance
“…Among menopausal and postmenopausal women, CEE therapy improves memory in some [16][17][18], but not all, studies [9,10]. Although other behavioral studies in rodents are lacking, in-vitro studies provide additional proof-ofconcept evidence that CEE may have beneficial neural effects.…”
Section: Discussionmentioning
confidence: 99%
“…Among menopausal and postmenopausal women, CEE therapy improves memory in some [16][17][18], but not all, studies [9,10]. Although other behavioral studies in rodents are lacking, in-vitro studies provide additional proof-ofconcept evidence that CEE may have beneficial neural effects.…”
Section: Discussionmentioning
confidence: 99%
“…They enhance the outgrowth of neurites and promote the formation of dendrite spines and synapses (Lustig, 1994;Woolley and McEwen, 1994). In the brain, estrogens increase cerebral blood flow and glucose metabolism and modulate acetylcholine metabolism (Bishop and Simpkins, 1995;Luine, 1985;Ohkura et al, 1995). Furthermore, the beneficial effect of estrogens on the CNS may be mediated by cholesterol and apo E…”
Section: Sex Steroidsmentioning
confidence: 99%
“…Many clinical studies have supported the therapeutic effect of estrogen on AD, since Fillit et al [20] first reported an open trial of estradiol-17b (E 2 ) therapy for AD (Table 2) [20][21][22][23][24][25][26][27][28][29][30][31][32]. However, the therapeutic effect was not established.…”
Section: ) Therapeutic Effect Of Estrogenmentioning
confidence: 99%